Populasi dan Habitat Rusa Timor (Cervus timorensis) - Rumakar, Saiful; Puttileihalat, M. M.S; Tuhumury, A. (MAKILA, 2019)
Deer including protected animals based on government regulation No. 7 of 1999 concerning Preservation of Plants and Animals. Animals that are in good habitat, are easy to breed and have multiple benefits, especially as a source of food, tourism objects and a place for the development of science and education and aesthetics. Therefore this study aims to analyze the population and habitat of timor deer in Banggoi Village, West Bula District, West Seram Regency. The results showed that the population and habitat used by the timor deer (Cervus timorensis) included mangrove forests, coastal forests, and grasslands. Timor deer (Cervus timorensis) provides food for the mangrove forest and grassland habitat, while for drinking needs, Timor deer consumes river water and at the edges of the water puddles in mangrove forests, coastal forests and grasslands. Places used as beds are mangrove roots, on the sand near the beach, and also alang-alang grass (Imperata cylindica). The resting places can be found during the research, namely the presence of deer feathers attached and also the appearance of the surface of the litter is decreased due to the piercing of the deer's body. In addition there are also veses (dirt) in places of rest.